Penerapan Metode Clustering pada Status Gizi Ibu Hamil : (Studi Kasus: Puskesmas Kota Datar) - Hesty Vitara; Rusmin Saragih; Victor Maruli Pakpahan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Pregnancy is a process in a woman's life, where major changes occur in her physical, mental and social aspects. These changes cannot be separated from the factors that influence them, namely physical factors, psychological factors and environmental, social, cultural and economic factors. One of the nutritional problems of pregnant women is chronic energy deficiency (KEK). Chronic energy deficiency (KEK) is a nutritional problem caused by a lack of food intake over a long period of time, a matter of years. Datar City Health Center is one of the agencies that provides health services for the local community and helps resolve problems with the health and nutritional development of mothers and children to prevent problems with malnutrition in pregnant women. The aim of the research is to make it easier for agencies to manage data and obtain complete information about the nutritional status of pregnant women. From 20 data, 3 groups were obtained, Cluster 1 had 4 data on the nutritional status of pregnant women, Cluster 2 had 4 data on the nutritional status of pregnant women and Cluster 3 had 12 data on the nutritional status of pregnant women. And the largest group obtained was cluster 3 with the data group on the nutritional status of pregnant women found in the gestational age group (X), namely 14-27 weeks old, with screening results (Y) namely adequate nutrition, and the causal factors (Z) that occurred were economic factors